2013
DOI: 10.1063/1.4804240
|View full text |Cite
|
Sign up to set email alerts
|

Electrical property measurements of Cr-N codoped TiO2 epitaxial thin films grown by pulsed laser deposition

Abstract: The temperature dependent resistivity and thermo-electric power of Cr-N codoped TiO2 were compared with that of single element N and Cr doped and undoped TiO2 using epitaxial anatase thin films grown by pulsed laser deposition on (100) LaAlO3 substrates. The resistivity plots and especially the thermoelectric power data confirm that codoping is not a simple sum of single element doping. However, the negative sign of the Seebeck coefficient indicates electron dominated transport independent of doping. The narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Experiments by Chiodi et al showed that Cr-N co-doping into nano-clustered TiO 2 thin films occurs on the substitutional sites and delocalized states are created inside the band-gap [128], consistent with earlier theoretical predictions [118]. In addition, experimental observations by Jaćimović et al showed that the effect of Cr-N codoping largely depends on the growth condition, implying the critical role of structural defects in the doping process [129]. Wang et al confirmed that co-doped Cr and N should both be substitutionally doped into TiO 2 , and the band-gap is narrowed to less than 2 eV, mainly owing to lifting of the VBM [130].…”
Section: Tiosupporting
confidence: 59%
“…Experiments by Chiodi et al showed that Cr-N co-doping into nano-clustered TiO 2 thin films occurs on the substitutional sites and delocalized states are created inside the band-gap [128], consistent with earlier theoretical predictions [118]. In addition, experimental observations by Jaćimović et al showed that the effect of Cr-N codoping largely depends on the growth condition, implying the critical role of structural defects in the doping process [129]. Wang et al confirmed that co-doped Cr and N should both be substitutionally doped into TiO 2 , and the band-gap is narrowed to less than 2 eV, mainly owing to lifting of the VBM [130].…”
Section: Tiosupporting
confidence: 59%
“…For example, a series of metal ions have been used to replace the Ti 4+ ions in the TiO 2 lattice to bring about visible-light absorption since the early 1990s, nonmetal elements have been adopted to replace the O 2À ions in the TiO 2 lattice since 2001, and metal and non-metal elements have been combined to replace partial Ti 4+ and O 2À ions in the TiO 2 lattice recently. [67][68][69][70][71][72][73][74] All these efforts have brought about the absorption of TiO 2 into the visible-light region and improved photocatalytic activity has been frequently reported.…”
Section: Lei Liumentioning
confidence: 99%
“…Three naturally occurring polymorphs-rutile, anatase, and brookite-are stable in atmosphere at high temperatures (rutile melts near 2100 K 1 while anatase and brookite transform irreversibly to rutile above approximately 900 K and 1100 K, respectively 2,3 ). Furthermore, large n-type Seebeck coefficients have been measured from -360 to -700 µV/K in rutile [4][5][6] and from -240 to -500 µV/K in anatase, [7][8][9][10][11] while power factors as high as 14 µW/(K 2 cm) have been reported. 12 Despite these promising characteristics, the highest reported value of the dimensionless thermoelectric figure of merit ZT = σS 2 T /κ to date is 0.35 at 973 K in rutile, 13 which is well below that of the current best thermoelectric materials.…”
mentioning
confidence: 95%
“…Pentavalent cation doping with Nb or Ta can achieve up to 8% cation substitution and produce free-carrier concentrations as high as 5×10 20 cm −3 for anatase. 16 High dopant concentrations increase the free-carrier concentration, electrical conductivity, and thermal conductivity while reducing the Seebeck coefficient, 7,12 exemplifying the trade-off that makes increasing ZT challenging.…”
mentioning
confidence: 99%